Community's Level of Knowledge and Attitude Concerning Tooth Extraction in Bonto Katute Village, Sinjai District - Puspitarini, Nurul Aisyiyah; Zulkarnaen, Zulkarnaen; Aisyah, Siti; Alfah, Sitti; Malaha, Naomi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
One of the treatments that can be done to treat dental and oral diseases is tooth extraction. Tooth extraction is an action that is often carried out in dental practice because most patients come with teeth that can no longer be treated. The obstacle experienced in tooth extraction efforts is the public's knowledge of things related to tooth extraction. Insufficient knowledge makes people hesitate to go to the dentist for treatment. This study aims to determine the level of knowledge and attitudes of the community regarding tooth extraction in Libureng village, Barru Regency. This research is descriptive with a cross-sectional design. The total sample of 87 respondents was obtained using the Slovin formula and simple random sampling. Data is presented in the form of a diagram based on frequency distribution. The results of the research show that the level of public knowledge about tooth extraction in Libureng village, Barru Regency, namely 55%, can be said to be good and the community's attitude towards tooth extraction at 69% can be said to be good. The conclusion is that the level of knowledge and attitudes of the people in Holidayeng village towards tooth extraction is classified as good.